Right Caputo Fractional Landau Inequalities - Anastassiou, George A. (Sarajevo Journal of Mathematics, 2024)
Right Caputo fractional $\left\Vert · \right\Vert _{p}$-Landau type inequalities, $p\in \left( 1,∞ \right] $ are obtained with applications on $\mathbb{R}_{-}$. 2000 Mathematics Subject Classification. 26A33, 26D10, 26D15